Distopia e subversão em O Ateneu de Raul Pompéia - Jareski, Lorenza Lakimé (2005)
The purpose of this dissertation is to study the O Ateneu by Raul Pompéia, written in 1888, during the promulgation of the Slavery Abolition (Lei Áurea) and just before the Proclamation of the Republic. The novel assumes a prominent position in the Brazilian Literature what reflects on the singularity of the criticism devoted to it. After the realization of Ateneu (a boarding school) as an oppressive world and the broken and complex reality of its characters, the author of this dissertation proposes another reading of the novel, under a dystopian literature view. The evaluation broadens under the deeds of some citizens of Ateneu which suggests a dissident status. The harsh fulfillment the laws and order in force at the boarding school demands a dissident behavior, for the survival of some characters, revealed in different ways of subversion, always limited by narrow boundaries in space and time. Sex, love, faith, art and family relations emerge in opposition to the school s reality. At last, this dissertation investigates the way Pompéia s narrative builds characters whose behavior flee from the acceptable Brazilian standards of the 1800 s patriarchal society, indicating rupture of established social order.